2012
DOI: 10.1242/dev.075390
|View full text |Cite
|
Sign up to set email alerts
|

Somatic small RNA pathways promote the mitotic events of megagametogenesis during female reproductive development in Arabidopsis

Abstract: SUMMARYFemale gamete development in Arabidopsis ovules comprises two phases. During megasporogenesis, a somatic ovule cell differentiates into a megaspore mother cell and undergoes meiosis to produce four haploid megaspores, three of which degrade. The surviving functional megaspore participates in megagametogenesis, undergoing syncytial mitosis and cellular differentiation to produce a multicellular female gametophyte containing the egg and central cell, progenitors of the embryo and endosperm of the seed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 34 publications
4
151
0
Order By: Relevance
“…The expression of Arabidopsis AGO5 is confined to the somatic cells around megaspore mother cells as well as in the megaspores, and a semidominant ago5 mutant is defective in the initiation of megagametogenesis (Tucker et al, 2012), suggesting that a somatic sRNA pathway mediated by AGO5 promotes megagametogenesis. AGO5 preferentially binds sRNAs with a 59 C that are derived from intergenic sequences (Mi et al, 2008), the function of which is largely unexplored.…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Arabidopsis AGO5 is confined to the somatic cells around megaspore mother cells as well as in the megaspores, and a semidominant ago5 mutant is defective in the initiation of megagametogenesis (Tucker et al, 2012), suggesting that a somatic sRNA pathway mediated by AGO5 promotes megagametogenesis. AGO5 preferentially binds sRNAs with a 59 C that are derived from intergenic sequences (Mi et al, 2008), the function of which is largely unexplored.…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
“…Arabidopsis AGO7 (also known as ZIP) specifically binds miR390 (Montgomery et al, 2008), which targets TAS3 transcripts (Bohmert et al, 1998;Morel et al, 2002;Vaucheret et al, 2004;Baumberger and Baulcombe, 2005;Qi et al, 2005;Zhang et al, 2006) ta-siRNAs vsiRNAs OsAGO1a Os02g45070 miRNAs Plant development, antiviral defense Os04g47870 miRNAs Plant development, antiviral defense (Wu et al, , 2015 (Takeda et al, 2008;Tucker et al, 2012;Brosseau and Moffett, 2015) vsiRNAs OsAGO5c Os03g58600 phasiRNAs Germ cell division (Nonomura et al, 2007;Komiya et al, 2014) AtAGO10 AT5G43810 miR165/166 SAM development, antiviral defense (Moussian et al, 1998;Lynn et al, 1999;Liu et al, 2009;Ji et al, 2011;Zhu et al, 2011;Garcia-Ruiz et al, 2015;Zhou et al, 2015) miR172 vsiRNAs (Harvey et al, 2011;Jaubert et al, 2011;Wang et al, 2011b;Zhang et al, 2011;Wei et al, 2012) vsiRNAs miR393* AtAGO3 AT1G31290 n.d. n.d. AtAGO7 AT1G69440 miR390 ta-siRNA biogenesis, phase transition, antiviral defense (Hunter et al, 2003;Adenot et al, 2006;Montgomery et al, 2008;Qu et al, 2008) OsAGO7 Os03g33650 miR390 ta-siRNA biogenesis, SAM development (Nagasaki et al, 2007) ZmAGO7 GRMZM5G892991 miR390 ta-siRNA biogenesis, leaf development (Douglas et al, 2010) AtAGO4 AT2G27040 hc-siRNAs DNA methylation, antibacterial immunity, defense against DNA viruses (Zilberman et al, 2003;Li et al, 2006;Pontes et al, 2006;…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Grafting experiments showed that PTGS was transmitted from 10027-3 rootstocks to leaf tissue of GFP-expressing scions (Fig. 1B) but not to GFP and YFP reporters expressed in pollen (Eady et al, 1994) or in female gamete precursor cells in developing ovules (Tucker et al, 2012;Supplemental Fig. S4; Supplemental Table S1).…”
Section: A Gfp Reporter System For Studying Systemic Ptgsmentioning
confidence: 99%
“…These different clades of AGO proteins engage in different small RNA pathways, with the AGO9 clade being active in the siRNA heterochromatin pathway that regulates the transcriptional silencing of transposons and repeats by mediating DNA methylation and heterochromatin formation (Mallory and Vaucheret, 2010). Increasing evidence highlights the importance of AGO activity in plant germline development and gamete formation (Nonomura et al, 2007;Wüest et al, 2010;Olmedo-Monfil et al, 2010;Singh et al, 2011;Borges et al, 2011;Tucker et al, 2012). This is reminiscent of the role of AGO proteins in the animal germline; proteins of the animal-specific PIWI-clade protect the genomic integrity of the germline, in particular by repressing the activity of transposons in invertebrates, although their role in vertebrates is less clear (Clark and Lau, 2014).…”
Section: The Acquisition and Restriction Of Reproductive Fatementioning
confidence: 99%
“…The expression patterns of proteins/genes whose perturbations mimic apomeiosis. The expression patterns or abundance of protein are schematically shown for: (A) MEL1 (Nonomura et al, 2007); (B) MEM (Schmidt et al, 2011); (C) AGO5 (Tucker et al, 2012) and AGO104 (Singh et al, 2011); and (D) AGO9 (Olmedo-Monfil et al, 2010). During female germline formation, MEL1 is expressed in the MMC, suggesting a cell-autonomous effect to cause failure of meiosis (Nonomura et al, 2007).…”
Section: The Acquisition and Restriction Of Reproductive Fatementioning
confidence: 99%